2024
DOI: 10.1177/17455057241240920
|View full text |Cite
|
Sign up to set email alerts
|

Urinary and reproductive tract infection symptoms and menstrual hygiene practices in refugee camps in Jordan: A cross-sectional study

Joud Al Karmi,
Mohammad Ali Alshrouf,
Tala A Haddad
et al.

Abstract: Background: Urinary tract infections and reproductive tract infections pose significant health risks, particularly among women living in challenging conditions. Unhygienic menstrual practices can exacerbate these risks, impacting physical and psychological well-being. Objectives: This study assessed the association between unhygienic menstrual care and self-reported urinary tract infection/reproductive tract infection symptoms among refugee women. In addition, it explored the association between these symptoms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
0
0
0
Order By: Relevance
“…Chronic exposure to inadequate menstrual hygiene can lead to recurring infections and other health issues, potentially exacerbating existing medical conditions and increasing healthcare needs over time. Previous study showed that high prevalence of urinary or reproductive tract infection symptoms among refugee menstruators and its association with poor menstrual hygiene practices [ 32 ]. In addition, the lack of hygienic menstrual management and limited access to affordable menstrual products, coupled with insufficient menstrual hygiene education, causes significant discomfort, psychological stress, and financial strain for women and girls [ 12 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chronic exposure to inadequate menstrual hygiene can lead to recurring infections and other health issues, potentially exacerbating existing medical conditions and increasing healthcare needs over time. Previous study showed that high prevalence of urinary or reproductive tract infection symptoms among refugee menstruators and its association with poor menstrual hygiene practices [ 32 ]. In addition, the lack of hygienic menstrual management and limited access to affordable menstrual products, coupled with insufficient menstrual hygiene education, causes significant discomfort, psychological stress, and financial strain for women and girls [ 12 , 33 ].…”
Section: Discussionmentioning
confidence: 99%